Distribution of Angiostrongylus vasorum and its gastropod intermediate hosts along the rural–urban gradient in two cities in the United Kingdom, using real time PCR. Issue 1 (December 2016) - Aziz, Nor; Daly, Elizabeth; Allen, Simon; Rowson, Ben; Greig, Carolyn; Forman, Dan; Morgan, Eric
Abstract Background Angiostrongylus vasorum is a highly pathogenic metastrongylid nematode affecting dogs, which uses gastropod molluscs as intermediate hosts. The geographical distribution of the parasite appears to be heterogeneous or patchy and understanding of the factors underlying this heterogeneity is limited. In this study, we compared the species of gastropod present and the prevalence ofA. vasorum along a rural–urban gradient in two cities in the south-west United Kingdom. Methods The study was conducted in Swansea in south Wales (a known endemic hotspot forA. vasorum ) and Bristol in south-west England (where reported cases are rare). In each location, slugs were sampled from nine sites across three broad habitat types (urban, suburban and rural). A total of 180 slugs were collected in Swansea in autumn 2012 and 338 in Bristol in summer 2014. A 10 mg sample of foot tissue was tested for the presence ofA. vasorum by amplification of the second internal transcribed spacer (ITS-2) using a previously validated real-time PCR assay. Results There was a significant difference in the prevalence ofA. vasorum in slugs between cities: 29.4 % in Swansea and 0.3 % in Bristol. In Swansea, prevalence was higher in suburban than in rural and urban areas. Comparing the sampled slug fauna, Arion rufus was found in greater numbers in Swansea than Bristol, and was commonly infected (prevalence 41 %). This, alongside the timing of slug collections in summer rather than autumn, could explain low infection prevalence in the Bristol sample. In the absence ofAr. rufus as a preferred host forA. vasorum, Ar. flagellus andLimacus maculatus appear to act as versatile hosts that are present in suburban and urban areas in Swansea (prevalence inAr. flagellus 33 %; inL. maculatus 44 %) and in Bristol (prevalence inAr. flagellus 0.9 %). These slug species might provideA. vasorum with an alternative vehicle to reach the final host, when the main hostAr. rufus is scarce or absent. Conclusion We conclude that the composition of the slug fauna varies spatially, and that this could help explain patchiness in the prevalence ofA. vasorum . A suburban peak was found in the prevalence of infection in intermediate hosts, perhaps explained by a higher density of competent intermediate and/or definitive hosts.